Philosopher's stone - "Gill, Ashim" (New Delhi, 2003)
The Philosopher's Stone attempts to reveal the hidden secrets that have bedevilled the philosophers for aeons. From Plato to Aristotle, to Descartes, Locke, Hume, Hegel and Kant; from Vivekananda, to Lao Tzu to the Buddha, The Philosopher's Stone attempts, in one mighty sweep, to reveal the great thoughts of great minds down the ages, both eastern and western, that have helped shape the human psyche.
Keywords: Philosophy